Studi Korelasi: Iklim Sekolah dengan Perilaku Perundungan Pada Siswa - Yusrah Annisa; Itto Nesyia Nasution; Muhammad Fadhli (Psychopolytan : Jurnal Psikologi, 2024)
The purpose of this research is to find the correlations of bullying behavior and school climate students at SMKN A. At this research, the total sample is 330 students and the sampling technique was in Proportionate Stratified Random Sampling. The measuring instruments used are the bullying behavior scale (20 items) and the school climate scale (25 items). The data analysis technique uses the product moment correlation technique. Based on the results of data analysis, the correlation coefficient (r) for -0.82 with a significance (p) of 0.000 (p < 0.05). Therefore, the hypothesat this research was accepted as the conclusion of the relationship in the direction of a negative between school climate and bullying behavior. The practical implication is that this research can be used as reference material for students to respond better to the school climate and as a guide in improving their social behavior at school.